Gender perspectives on coastal and marine ecosystems services flow in Kwale County, Kenya - Nyangweso Ochieng, Christine; Thenya, Thuita; Mwaura, Francis; Owuor, Margaret Awuor (Frontiers in Sustainable Food Systems, 2023)
Introduction The continuous flow of ecosystem services (ESs) within coastal and marine ecosystems supports communities' well-being and security by harnessing required resources such as seafood that address food security. The overexploitation of these coastal resources places communities at risk of losing ES. This study assesses how preference for the ES flow from these ecosystem types (i.e., mangrove forests, coastal lagoons, seagrass beds, coral reefs, and the deep sea) vary by gender in Diani Chale and Kisite-Mpunguti Marine Protected Areas in Kwale County, Kenya. Specifically, the objective of this article was to assess the pattern and variation in mean scores of ES flow across coastal and marine ecosystem types by gender. Methods A total of 148 respondents (87 men and 61 women) aged 20-72 years participated in describing ES through focus group discussions and the Delphi technique. Respondents were engaged in a participatory activity that involved filling of perceived ES flow scores using a 6-point Likert-type scale in the lookup tables (also known as matrix). Data were analyzed using descriptive statistics for mean scores of ES flow across coastal and marine ecosystem types as perceived by men and women. One-way MANOVA was used to test for the significant differences between mean scores of men and women in ES flow across ecosystem types. Results The aggregate scores for non-use values, regulating services, and cultural services, were scored higher than provisioning services by ecosystem service flow. The overall ES flow scores were higher in the mangrove forests 52/90 and least in the coastal lagoon 39/90. There was a significant variation (p < 0.05) of ES flow by gender: the mean score of men was significantly higher than women for most ES flow in cultural, regulating, and provisioning services across some coastal and marine ecosystem types. However, there was no significant variation (p > 0.05) in the flow of non-use values by gender across ET. Conclusion The findings of this study highlight the importance of understanding gender views in ES access and use at local levels to support food security. Including gender perspectives in coastal and marine ecosystem governance is critical, especially toward achieving sustainable development goals.